THE ROLE OF EDUCATION IN SHAPING INDIAN MARRIAGE AND FAMILY VALUES - Singh, Jyoti; Pandey, Ambika Prasad; Kumar, Nisheet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the role of education in transforming marriage and family values in the Agra district of Uttar Pradesh, India. Using a mixed-methods approach, 117 respondents were surveyed to examine how education impacts marriage choices, gender roles, and family structures. The analysis, conducted using descriptive statistics, ANOVA, and correlation matrices, reveals that higher education promotes autonomy in marriage decisions, supports gender equality within households, and encourages a shift from traditional joint family systems to nuclear families. The findings suggest that education is a key driver of social change, aligning with national trends observed in urban areas. And, regional disparities remain, especially in rural and semi-urban regions, where access to education is limited, and traditional values persist. The study emphasizes the need for expanded educational access and gender equality programs to further foster progressive family dynamics in underrepresented areas. Future research should focus on exploring these regional differences and the broader implications of education on family and societal structures.